Nurse Trend in Writing Objectives and Outcome Criteria of Nursing Diagnosis in Patients With Pulmonary Tuberculosis at The Government Hospital in Salatiga Indonesia - Muhamad Rofii; Bambang Edi Warsito; Agus Santoso; Sarah Ulliya (Universitas Muhammadiyah Semarang, 2019)
Background. Writing nursing goals and outcome criteria found in nursing care documentation was very varied and not appropriately, it needs to be explored more deeply about the phenomenon. The Study objective was to determine the writing of nursing goals and the outcome criteria for nursing diagnoses. Methods. Research design was qualitative research with a direct observation approach. Data was taken in the MDR TB ward, samples were 100 documentation of pulmonary TB patients. Sampling technique was nonprobability sampling. Result. The goal of nursing diagnosis of ineffective airway clearance was airway clearance effectively again, the problem was resolved, the patient's airway returned to normal and coughing the patient returns to normal, etc. The goal of nursing diagnosis of ineffective breathing patterns was effective breathing patterns, ineffective breathing patterns resolved, etc. The outcome criteria of nursing diagnosis ineffective airway clearence was negative cough, normal respiratory rate, normal vital signs, negative sputum, shortness of breath, coughing resolved, comfortable patients, patients can demonstrate coughing effectively, sputum can come out, breath was relieved, sputum can come out, etc. The outcome criteria for nursing diagnosis ineffective breathing patterns are normal respiratory rate, normal vital signs, respiratory rate was 20 x/minute, it was not weakness, It was not nausea, etc. Recomendation. Nurses are advised to be given trainings, sosialisation, or workshops related to the goals and outcome criteria of nursing diagnoses, and are expected to use NANDA and NIC-NOC references.